Cultural adaptation and reproducibility validation of the Brazilian Portuguese version of the Pain Assessment in Advanced Dementia (PAINAD-Brazil) scale in non-verbal adult patients - Marcia Carla Morete Pinto; Fabiola Peixoto Minson; Ana Carolina Biagioni Lopes; Claudia Regina Laselva (Einstein (São Paulo))
Objective To adapt the Pain Assessment in Advanced Dementia (PAINAD) scale to Brazilian Portuguese with respect to semantic equivalence and cultural aspects, and to evaluate the respective psychometric properties (validity, feasibility, clinical utility and inter-rater agreement). Methods Two-stage descriptive, cross-sectional retrospective study involving cultural and semantic validation of the Brazilian Portuguese version of the scale, and investigation of its psychometric properties (validity, reliability and clinical utility). The sample consisted of 63 inpatients presenting with neurological deficits and unable to self-report pain. Results Semantic and cultural validation of the PAINAD scale was easily achieved. The scale indicators most commonly used by nurses to assess pain were “Facial expression”, “Body language” and “Consolability”. The Brazilian Portuguese version of the scale has proved to be valid and accurate; good levels of inter-rater agreement assured reproducibility. Conclusion The scale has proved to be useful in daily routine care of hospitalized adult and elderly patients in a variety of clinical settings. Short application time, ease of use, clear instructions and the simplicity of training required for application were emphasized. However, interpretation of facial expression and consolability should be given special attention during pain assessment training.